CALCULATION OF SPECIAL FUNCTIONS WITH ARBITRARY PRECISION IN THE .NET FRAMEWORK ENVIRONMENT - Aynakulov Toxir Turg‘un o‘g‘li; Norqo‘ziyev Quvonchbek Komiljon o‘g‘li; Irgasheva Umida Abdimital qizi; Abdurashidova Lobar Ulug‘bek qizi (Лучшие интеллектуальные исследования, 2024)
Annotation Abstract: The paper describes the methods and algorithms used for realization of special functions computing with arbitrary precision in the environment of .NET Framework. .NET Framework C# is used as a tool, with the help of the MPIR library. An example is demonstrated, with a program, using the current state of the special functions library realization. Some perspectives for future development are outlined.